Disubstituted piperazine analogues of trifluoromethylphenylpiperazine and methylenedioxybenzylpiperazine: analytical differentiation and serotonin receptor binding studies - Jack DeRuiter; Ashleigh Van Cleave; Audinei de Sousa Moura; Younis Abiedalla; C. Randall Clark (Oxford University Press, 2018)
A series of N,N-disubstituted piperazines were synthesized containing the structural elements of both methylenedioxybenzylpiperazine (MDBP) and trifluoromethylphenylpiperazine (TFMPP) in a single molecule. These six potential designer drug molecules having a regioisomeric relationship were compared in gas chromatography-mass spectrometry (GC-MS), gas chromatography-infrared spectroscopy and serotonin receptor affinity studies. These compounds were separated by capillary gas chromatography on an Rxi®-17Sil MS stationary phase film and the elution order appears to be determined by the position of aromatic ring substitution. The majority of electron ionization mass spectral fragment ions occur via processes initiated by one of the two nitrogen atoms of the piperazine ring. The major electron ionization mass spectrometry (EI-MS) fragment ions observed in all six of these regioisomeric substances occur at m/z = 364, 229, 163 and 135. The relative intensity of the various fragment ions is also equivalent in each of the six EI-MS spectra. The vapour phase infrared spectra provide a number of absorption bands to differentiate among the six individual compounds on this regioisomeric set. Thus, the mass spectra place these compounds into a single group and the vapour phase infrared spectra differentiate among the six regioisomeric possibilities. All of the TFMPP-MDBP regioisomers displayed significant binding to 5-HT2B receptors and in contrast to 3-TFMPP, most of these TFMPP-MDBP isomers did not show significant binding at 5-HT1 receptor subtypes. Only the 3-TFMPP-3,4-MDBP (Compound 5) isomer displayed affinity comparable to 3-TFMPP at 5-HT1A receptors (Ki = 188 nmol/L).